THE EFFECTS OF MULTIMEDIA PRESENTATION ON MALAY IDIOM LEARNING - TUN ARISSA, TUN MOHAMED KAMARUL (Universiti Malaysia Sarawak (UNIMAS), 2020)
The present study determined the effects of multimedia presentation on Malay Language idiom learning. For this experiment, 30 undergraduate students with access to internet were asked to participate in this experiment by learning and understanding a series of Malay Language idioms through one of the two types of multimedia presentation, image and narration (IN) or image, narration and on-screen text (INT). From the result of the independent t-test displayed that there is no significant difference in terms of performance between the two groups and that both group’s participants managed to perform equivalently. Nonetheless, participants from the image, narration, and on-screen text group (INT) performed slightly better according to the slight difference in mean reading than the image and narration group (IN), indicating the additional element of on-screen text in INT aid in learning and understanding on Malay Language Idioms for the undergraduate students. The present study proved that for either image and narration (IN) or image, narration and onscreen text (INT), it is in the will power of the learners to have a better understanding towards Malay idioms when they best match the learning styles of the learners themselves.